(untitled) (Nigerian Journal of Technology, 2018)
ABSTRACT Natural fibres have good weight-to-strength ratio which has made it a material of interest for scientists and engineers. However, the major drawback for outdoor application of natural fibres is its hydrophilic nature. In this study, attempt was made to render bamboo fibre hydrophobic through acetylation with acetic anhydride at room temperature. The functional water absorption properties were studied and the acetylation parameters, such as chemical dosage and acetylation time, were optimised. Taguchi Orthogonal Array was used for the experimental design. Based on the Taguchi design, a regression equation was generated which served as an objective function for Genetic Algorithm. Acetylation reduced the percentage water absorption of Bambusa Vulgaris fibre from 196.4% in un-acetylated fibre down to 45% in acetylated fibres within the feasible design space. The optimal parameter setting generated with genetic algorithm is 15% acetic acid concentration, 50minutes of time soaked in acetic acid, 5% acetic anhydride concentration and 30 minutes time soaked in acetic anhydride. Under the optimum condition, the percentage water absorption was 44%. A confirmation experiment validated the effectiveness of the Genetic Algorithm result. Keywords: Acetylation, Bamboo Fibre, Taguchi, Optimisation, Genetic Algorithm http://dx.doi.org/10.4314/njt.v38i1.14